Your strategy needs a strategy how to choose and execute the right approach - Reeves, Martin; Haanaes, Knut; Sinha, Janmejaya Kumar 1959- (Ascent Audio, 2023)
Executives are bombarded with bestselling ideas and best practices for achieving competitive advantage, but many of these ideas and practices contradict each other. Should you aim to be big or fast? Should you create a blue ocean, be adaptive, play to win-or forget about a sustainable competitive advantage altogether? In a business environment that is changing faster and becoming more uncertain and complex almost by the day, it's never been more important-or more difficult-to choose the right approach to strategy. In this book, The Boston Consulting Group's Martin Reeves, Knut Haanæs, and Janmejaya Sinha offer a proven method to determine the strategy approach that is best for your company. They start by helping you assess your business environment-how unpredictable it is, how much power you have to change it, and how harsh it is-a critical component of getting strategy right. They show how existing strategy approaches sort into five categories-Be Big, Be Fast, Be First, Be the Orchestrator, or simply Be Viable-depending on the extent of predictability, malleability, and harshness. In-depth explanations of each of these approaches will provide critical insight to help you match your approach to strategy to your environment, determine when and how to execute each one, and avoid a potentially fatal mismatch.